AN ANALIYSIS OF STUDENTS’ ABILITY IN IDENTIFYING MAIN IDEA IN NARRATIVE PARAGRAPH OF THE FIRST GRADE AT SMA PUTERI SION MEDAN - Deniati Sitohang; Damerita Damanik; Kembar Rosari Capah; Resperdiana Purba (STKIP Persada Khatulistiwa Sintang, 2021)
This study aims to provide an overview of the analysis of class X SMA Putri Sion Medan in identifying and knowing the difficulties experienced by class X Puteri Sion students in determining the main ideas in the narrative paragraphs. This research uses a qualitative approach,and the tool of data collection was used written test. The sample consisted of 11 students. In conducting the research, the researcher got the result that the students' ability to identify main ideas in narrative paragraphs was in a very bad category. Based on the analyzed data, it was found that 3 students (27.28%) got a score of 81-90 (very good), 1 student (9.09%) got a score of 61-70 (enough), 2 students (18.18%) got a score grades 51-60 (poor), and 5 students (45.44%) scored less than 50 (very bad). Most of the students scored in the very poor category. After analyzing the ability to identify main ideas in narrative paragraphs, it is known that the ability to identify main ideas in class X Puteri Sion Medan is in a very bad category. The difficulties that students face when identifying the main idea in a narrative paragraph are a lack of interest in learning that makes them lazy to read, lack of vocabulary knowledge, their vocabulary is very small, and poor reading strategies.Keywords: Analysis, students’ ability, narrative Text